An Ethical View of Speculation - González-Carvajal Santabárbara, Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
After briefly explaining what speculation is, and its effects, it follows an ethical discernment. Although a small amount may be healthy, the actual levels of speculation have proved dangerous for the world economy. In the actual economic debate ¿What can be said from an ethical point of view?